TiO2-x films as a prospective material for slab waveguides prepared by atomic layer deposition. (February 2023) - Jurado-González, J.A.; Lizárraga-Medina, E.G.; Vazquez, J.; Romo, O.; López, J.; Contreras-López, O.E.; Nedev, N.; Márquez, H.; Tiznado, H.
Highlights: Fabrication of TiO2-X optical waveguides, controlling oxygen vacancies. Refractive index calculation for TiO2-X films by REELS and Ellipsometry. TiO2-X optical waveguides with propagation losses less than 1 dB/cm. Abstract: The refractive index is the most important property of materials with potential in waveguides since this determines essential parameters such as propagation modes and losses in the first instance. Therefore, studying new materials with a high refractive index (>2) continues to be a field of study. One of the candidate materials is TiO2 since it has a high refractive index (>2.2), high long-term stability, and low commercial cost. Furthermore, the possibilities with TiO2 can improve if the oxygen vacancies are created, which leads to high refractive indices (>2.4). For waveguides, this is a material with high added value. However, the increase in oxygen vacancy content could produce high absorption of light (>50 %), so it is necessary to explore the limits of light propagation in this material. In this work, we fabricate TiO2-x films by atomic layer deposition (ALD) and explore the limits of its application as a waveguide. The most relevant observations indicate that the accumulation of oxygen vacancies occurs cycle-by-cycle and that the refractive index can increase up to 2.8. However, transmittance becomes zero. The best propagation loss result (less than 0.5 dB/cm) for waveguide applications was obtained with a TiO2-x film with refractive index of 2.55. The discussion was based on the physicochemical and optical characterization employed by SEM, AFM, XRD, XPS, REELS, UV–Vis Transmittance, Ellipsometry, Impedance spectroscopy, and the four-point method. Our results reveal the high value of TiO2-x and the ALD technique in photonics.